Postgraduate training for the management of the health technologies evaluation from a theoretical perspective - Irela Yolaidys Pérez Andrés; Nadina Travieso Ramos (Centro Provincial de Información de Ciencias Médicas, 2019)
Health professionals play a key role in the rational use and regulation of the available health resources. The theoretical bases and the historical tendencies that characterize the postgraduate training of the science, technology and innovation in health agents for the management of the health technologies evaluation are presented in this work. The training postgraduate concept for the management of the health technologies evaluation is defined. The three stages which have characterized the course of this process, associated with the demands coming from the historical context of the development of this activity in the health institutions are determined. It was verified that a methodological theoretical proposal that allows the appropriation, updating and deepening in the knowledge and skills for the management of the health technologies evaluation doesn't exist.